Anti-coagulase-negative Staphylococcus activity of ethanolic extracts of propolis from two Brazilian regions and synergism with antimicrobial drugs by the E-test method - R. P. Mantovani; V. L. M. Rall; J. E. N. Batalha; A. A. H. Fernandes; A. Fernandes Junior (Journal of Venomous Animals and Toxins including Tropical Diseases, 2008)
Propolis is a natural resinous substance collected by bees from vegetal sources and its therapeutic properties have been investigated. In this work, we evaluated the inhibitory activity of ethanolic extracts of propolis (EEP) from the Southeast and South of Brazil on coagulase-negative Staphylococcus (CNS) growth as well as the EEP in vitro synergism with antimicrobial drugs by using the diffusion method (E-test). The EEP chemical characteristics (dry weight, pH, flavonoid and phenolic compounds) were determined. Seven drugs were tested, and synergism was observed between three drugs and Southeast EEP, six drugs and South EEP, and one drug and ethanol control. Ethanolic extracts of propolis from the South of Brazil presented the greatest flavonoid content and synergism rate, while EEP from the Southeast presented the greatest anti-CNS activity and phenolic compound content. Results showed the correlation among anti-CNS activity, synergism rate and chemical characteristics of propolis.